High homocysteine, low vitamin B-6, and increased oxidative stress are independently associated with the risk of chronic kidney disease - Chen, Cheng-Hsu; Yang, Wen-Ching; Hsiao, Yu-Hua; Huang, Shih-Chien; Huang, Yi-Chia (Nutrition (Burbank, Los Angeles County, Calif.), 2016)
Hyperhomocysteinemia, increased oxidative stress, and decreased antioxidant defense function have been found to be associated with the risk of chronic kidney disease (CKD). Deficiencies of folate and vitamin B-6 (pyridoxal 5′-phosphate, PLP) may cause hyperhomocysteinemia and increased oxidative stress. The purpose of this study was to determine the associations among homocysteine, folate, PLP, oxidative stress indicator, and antioxidant capacities in patients with stage 2 to 3 CKD, and to further analyze these relationships with respect to risk for CKD. Ninety-seven patients with CKD and 135 healthy subjects were recruited. Patients with CKD had significantly higher levels of malondialdehyde and total antioxidant capacities, but had significantly lower antioxidant enzyme activities compared with healthy subjects. Serum folate but not plasma PLP was significantly negatively associated with plasma homocysteine. There were no significant associations of homocysteine, PLP, and folate with oxidative stress indicator and antioxidant capacities. High homocysteine (odds ratio [OR] = 1.11; 95% confidence interval [CI], 1.02–1.22) and malondialdehyde (OR = 34.24; 95% CI, 4.44–264.40) level increased the risk of CKD, whereas high plasma PLP (OR = 0.98; 95% CI, 0.97–0.99) and superoxide dismutase activity (OR = 0.82; 95% CI, 0.74–0.91) decreased the risk of CKD after adjusting all potential confounders. High homocysteine, low PLP, increased oxidative stress, and decreased antioxidant enzyme activity (superoxide dismutase activity) were independent contributing factors in the development of early stage CKD. •This was a case-control study, and 97 patients with chronic kidney disease and 135 healthy subjects were recruited.•Case subjects had significantly higher plasma homocysteine and oxidative stress but lower serum folate and plasma pyridoxal 5′-phosphate concentrations than control subjects.•We found that high plasma homocysteine, low vitamin B-6, increased oxidative stress, and decreased antioxidant enzyme activity were independently contributed to development of early stage chronic kidney disease.